Uncovering Violence Reading Biblical Narratives as an Ethical Project. - Cottrill, Amy (Presbyterian Publishing Corporation, 2021)
Uncovering Violence seeks to provide a theoretical vocabulary for the various forms that violence can take-including textual violence, interpretive violence, moral injury, and slow violence-and to offer a fresh ethical reading of violence in the biblical text.